Metamodeling Methodology for Modeling Cyber-Physical Systems. Issue 4 (18th May 2016) - Mezhuyev, Vitaliy; Samet, Refik
ABSTRACT: Existing metamodeling approaches cannot effectively capture the properties of heterogeneous and multidimensional cyber-physical domains. To contribute to this area, a new metamodeling methodology for the development of metamodels with different mathematical semantics is proposed in this article. The new metamodeling architecture and the method for the development of metamodels as integrated formal systems are discussed. To prove the concept, a geometrical meta-metamodel, which allows linking physical properties of multidimensional domains with their spatial structures, is proposed.